ANALYSIS OF THE EFFECTIVENESS OF PBB-P2 AND ITS CONTRIBUTION TO THE REGIONAL ORIGINAL REVENUE IN BANDUNG REGENCY - Aisyah, Meira; Amrania, Gia Kardina Prima (LPPM Univ. Ibn Khaldun Bogor, 2025)
The Rural and Urban Land and Building Tax (PBB-P2) is one of the main sources of Regional Original Revenue (PAD) in Bandung Regency. This study analyzes the effectiveness of PBB-P2 revenue and its contribution to PAD during the 2019-2023 period. The results of the analysis show that although the potential PBB-P2 revenue is high, the realization of revenue fluctuates, where in 2019-2021 the target was achieved, but decreased in 2022-2023. Factors such as taxpayer compliance, administrative systems, and local fiscal policies affect target achievement. The programs owned by the Bandung Regency Regional Revenue Agency have a positive impact on increasing taxpayer compliance, but are not optimal enough to increase revenue effectiveness. Overall, the contribution of PBB-P2 to PAD is still relatively low, ranging from 9%-11% annually. Therefore, a more comprehensive strategy is needed to optimize local tax revenue to increase its effectiveness and contribution to PAD.